Contaminating reactivity of a monoclonal CCAAT/Enhancer Binding Protein β antibody in differentiating myoblasts - AlSudais, Hamood; Wiper-Bergeron, Nadine (Université d'Ottawa | University of Ottawa, 2019)
Abstract Objective CCAAT/Enhancer Binding proteins (C/EBPs) are transcription factors involved in the regulation of a variety of cellular processes. We used the Abcam Recombinant Anti-C/EBP beta antibody (E299) to detect C/EBPβ expression during myogenesis. Though the antibody is monoclonal, and the immunogen used is highly specific to C/EBPβ, we identified an intense band at 23 kDa on western blot that did not correspond to any of the known isoforms of C/EBPβ, or family members predicted to cross-react. Absent in myoblast cells overexpressing C/EBPβ, the band was present when C/EBPβ was knocked down, confirming specificity for a protein other than C/EBPβ. The objective of this work was to identify the contaminating reactivity. Results We performed immunoprecipitation followed by mass spectrometry to identified myosin light chain 4 (MYL4) as the unknown band, suggesting that the Abcam monoclonal antibody directed against C/EBPβ is not pure, but contains a contaminating antibody against MYL4. Caution should be used when working in cells lines that express MYL4 to not confound the detection of MYL4 with that of C/EBPβ isoforms.